Coordination, Organizations, Institutions, Norms, and Ethics for Governance of Multi-Agent Systems XIV: International Workshop, COINE 2021, London, UK, May 3, 2021, Revised Selected Papers - Theodorou, Andreas; Nieves, Juan Carlos; De Vos, Marina (Lecture Notes in Computer Science, 2022)
This book constitutes revised selected papers from the thoroughly refereed proceedings of the International Workshop on Coordination, Organizations, Institutions, Norms, and Ethics for Governance of Multi-Agent Systems XIV, COINE 2021, held in London, UK, May 3, 2021.  The 9 full papers included in this book were carefully reviewed and selected from 12 submissions. They were organized in topical sections as follows: Invited talk; conceptual frameworks architectures for collaboration and coordination; and modelling and understanding social behaviour using COINE technologies.